2012
DOI: 10.1002/hed.23065
|View full text |Cite
|
Sign up to set email alerts
|

A new angle to mandibular reconstruction: The scapular tip free flap

Abstract: The natural scapular angle makes the scapular tip flap ideal for mandibular angle reconstruction. Short bone segments can be harvested with little donor-site morbidity. The long pedicle length may obviate vein grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 40 publications
2
51
0
2
Order By: Relevance
“…Several authors have noted that hardware exposure occurred at a higher rate in patients who underwent osseocutaneous radial forearm free flaps (OCRFFF) versus fibular free flaps (FFF), and concluded that this was likely due to the smaller amount of soft tissue incorporated in the OCRFFF (Day et al, ; Dean et al, ; Virgin et al, ). The subscapular system of free flaps makes available considerable soft tissue bulk with excellent mobility of the soft tissue relative to the bony component and generally provides abundant soft tissue coverage of the reconstruction plate (Gibber et al, ; Urken et al, ; Yoo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have noted that hardware exposure occurred at a higher rate in patients who underwent osseocutaneous radial forearm free flaps (OCRFFF) versus fibular free flaps (FFF), and concluded that this was likely due to the smaller amount of soft tissue incorporated in the OCRFFF (Day et al, ; Dean et al, ; Virgin et al, ). The subscapular system of free flaps makes available considerable soft tissue bulk with excellent mobility of the soft tissue relative to the bony component and generally provides abundant soft tissue coverage of the reconstruction plate (Gibber et al, ; Urken et al, ; Yoo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Osseocutaneous free tissue transfer with titanium plate fixation is now considered the standard of care for mandibular reconstruction (Bak, Jacobson, Buchbinder, & Urken, ). High rates of success of microvascular free flap reconstructions approaching 100% have been reported in literature for fibular and scapular free flaps (Dowthwaite et al, ; Hidalgo & Pusic, ; Urken et al, ; Urken, Bridger, Zur, & Genden, ; Wei, Seah, Tsai, Liu, & Tsai, ; Yoo, Dowthwaite, Fung, Franklin, & Nichols, ). Continuing improvements in surgical techniques and fixation hardware have greatly assisted with this success; however, hardware complications and failures persist.…”
Section: Introductionmentioning
confidence: 99%
“…The long pedicle length was found to be an advantage, as no vein grafts were required. 66 The scapular system affords a variety of harvest configurations, using a medial or lateral scapular crests, and including with a thoracodorsal artery perforator flap as mentioned above; the donor site morbidity is well tolerated. 63 …”
Section: Scapula Free Flapmentioning
confidence: 99%
“…The thin bone precludes dental implantation, unless the scapular bone is oriented in a vertical position; however, the scapular bone is generally considered inferior to the iliac crest for this indication. 32 Radial forearm free flap The radial forearm free flap is based on the radial artery and its comitant veins. It has a reliable, long pedicle with excellent soft tissue properties for oral lining coverage because of its large, thin, pliable skin paddle (up to 64 cm 2 ).…”
Section: Fibula Free Flapmentioning
confidence: 99%